Large-Scale Sea Urchin Culling Drives the Reduction of Subtidal Barren Grounds in the Mediterranean Sea - Guarnieri, Giuseppe; Bevilacqua, Stanislao; Figueras, Neus; Tamburello, Laura; Fraschetti, Simonetta (Frontiers in Marine Science, 2020)
Increasing anthropogenic pressures are causing long-lasting regime shifts from high-diversity ecosystems to low-diversity ones. In the Mediterranean Sea, large extensions of rocky subtidal habitats characterized by high diversity have been completely degraded to barren state due to high grazing pressure exerted by sea urchins, which could persist for long time. In several areas of the world, a positive effect of sea urchin removal on the recovery of overexploited subtidal rocky habitats was found. This study assessed, for the first time in the Mediterranean Sea, the effects of extensive sea urchin culling on the recovery of subtidal reefs from the state of barrens. We tested this approach within a Marine Protected Area where a combination of oligotrophic conditions, general depletion of fish stocks, dramatically high sea urchin densities, and the large extension of barren grounds caused by date mussel fishery hampered the natural recovery of shallow rocky reefs. Culling intervention (through hammering) was carried out in spring 2015, covering an area of 1.2 hectares at about 5 m depth. The effects of sea urchin removal were monitored at regular intervals, for a time span of 3 years, and were compared with two control sites adjacent to the culling area. We documented a progressive reduction of the barren grounds in the fully protected area after the intervention. Also, very low re-colonization of sea urchins was observed during the experiment, so that no additional extensive culling was necessary. Our findings suggested sea urchin culling as a promising practice, also considering the limited costs of the intervention. However, since the reduction of barren grounds was largely driven by turf forming algae, caution is needed in the interpretation of the outcomes in terms of restoration, and results are discussed considering the factors involved in the observed shift and the synergies to be carried out for a full recovery of the system.